Pemberdayaan Masyarakat Melalui Progam Sekolah Perempuan Berdayakan Lindungi Perempuan dan Anak (Sekoper Berlian) di Desa Tambakrejo Jombang - Esti Puji Rahayu; Sri Wibawani (Reslaj: Religion Education Social Laa Roiba Journal, 2025)
Implementation of community empowerment is one form of effort to achieve social welfare. In this case, to achieve social welfare, the Jombang Regency Government implemented the Women's School program to empower and protect women and children (SEKOPER BERLIAN) in Tambakrejo Village, Jombang District, Jombang Regency. The purpose of this study was to describe and analyze the Implementation of the Women's School Program to Empower and Protect Women and Children (SEKOPER BERLIAN) in Tambakrejo Village, Jombang. This study used a qualitative research method with a descriptive approach. The results of this study based on the factors that determine the success of policy implementation according to Erwan and Dyah consist of 6 factors, namely: (1) policy quality; (2) adequacy of policy input; (3) instrument accuracy; (4) implementor capacity; (5) characteristics and support of target groups; (6) geographic, social, economic, and political environmental conditions can be implemented properly. Therefore, it is concluded that the Women's School Empowering Protecting Women and Children (SEKOPER BERLIAN) program in Tambakrejo Village, Jombang can be successfully implemented so that the policy objectives can be achieved.